(untitled) (British Journal of Global Ecology and Sustainable Development, 2026)
The aim of this study was to evaluate the immediate and long-term treatment outcomes in patients with diffuse large B-cell lymphoma (DLBCL) with extranodal involvement and to identify key prognostic factors affecting disease outcome.